Gigantism and acromegaly : genetics, diagnosis, and treatment - Stratakis, Constantine A. (Academic Press, 2021)
Gigantism and Acromegaly brings together pituitary experts, taking readers from bench research, to genetic analysis, clinical analysis, and new therapeutic approaches. This book serves as a reference for growth hormone over-secretion and its diagnosis and treatment for endocrinologists, pediatricians, internists, and neurosurgeons, and for geneticists. Pharmaceutical companies may use it as a reference for drug development and research. Students, residents and fellows in medicine and endocrinology and genetics will also find it valuable as it provides a single up-to-date review of the molecular biology of gigantism and acromegaly as well as recommended approaches to evaluation and management. Acromegaly is a rare pituitary disorder that slowly changes its adult victim's appearance over time: larger hands and feet, bigger jaw, forehead, nose, and lips. Generally, a benign pituitary tumor is the cause and symptoms of acromegaly can vary from patient to patient, making a diagnosis difficult and prolonging suffering for years. Early detection is key in the management of acromegaly as the pathologic effects of increased growth hormone (GH) production are progressive and can be life-threatening as the result of associated cardiovascular, cerebrovascular, and respiratory disorders and malignancies.